A protective rung on the ladder? How past and current social status shaped changes in health during COVID-19. (March 2022) - Upenieks, Laura; Schieman, Scott; Meiorin, Rachel
Abstract: An emerging body of work has started to document population health consequences of the social and economic transformations during the COVID-19 pandemic. We consider an individual's relative social position in the stratification system—subjective social status (SSS)—and assess how past (childhood) and current SSS predict change in self-rated health during the pandemic. Using two waves of data from the Canadian Quality of Work and Economic Life Study, we follow respondents between the onset of lockdown measures in March and May of 2020 (N = 1886). Drawing from the life course perspective and stress process model, we find that lower current SSS predicts a greater likelihood of being in stable poor health and reporting declining health. Lower past SSS predicts a higher chance of being in stable poor health indirectly through current SSS. And lower cumulative SSS that sums both past and present SSS also predicts stable poor health, while perceived upward mobility over time is associated with stable good health. This robust relationship between SSS and health in such a short time period of two months at the start of the COVID-19 pandemic provides an important glimpse into the influence that SSS has on population health. Highlights: Using two waves of data from the Canadian Quality of Work and Economic Life Study, we follow respondents between the onset of lockdown measures in March and May of 2020 (N = 1886). Drawing from the life course perspective and stress process model, we find that lower current SSS predicts a greater likelihood of being in stable poor health and reporting declining health. Lower past SSS predicts a higher chance of being in stable poor health indirectly through current SSS. And lower cumulative SSS that sums both past and present SSS also predicts stable poor health, while perceived upward mobility over time is associated with stable good health.